2016
DOI: 10.1021/acsami.6b00957
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Aligned Conducting PPy-PLLA Fiber Films and Their Electrically Controlled Guidance and Orientation for Neurites

Abstract: Electrically conductive biomaterial scaffolds have great potential in neural tissue regeneration. In this work, an aligned conductive fibrous scaffold was prepared by electrospinning PLLA on rotating collector and chemical oxidation polymerization of pyrrole (PPy) codoped with poly(glutamic acid)/dodecyl benzenesulfonic acid sodium. The characterization results of composition, structure and mechanics of fiber films show that the existence of weak polar van der Waals' force between PPy coating and PLLA fibers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 38 publications
(80 reference statements)
5
58
0
Order By: Relevance
“…Effects of anisotropic topographies in guiding and promoting the neurite growth are consistent with results observed for SH‐SY5Y cells grown onto aligned fibers and ridges . Nevertheless, the combined effect of electrical and guidance cues was reported to enhance the neurite outgrowth in neuron‐like PC12 cells, stimulated through polypyrrole‐coated aligned sub‐micrometric fibers . In particular, enhancements in terms of fraction of neurite‐bearing cells (124%) and of neurite length (66% and 129%) were reported with respect to nonstimulated cells onto randomly oriented fibers.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Effects of anisotropic topographies in guiding and promoting the neurite growth are consistent with results observed for SH‐SY5Y cells grown onto aligned fibers and ridges . Nevertheless, the combined effect of electrical and guidance cues was reported to enhance the neurite outgrowth in neuron‐like PC12 cells, stimulated through polypyrrole‐coated aligned sub‐micrometric fibers . In particular, enhancements in terms of fraction of neurite‐bearing cells (124%) and of neurite length (66% and 129%) were reported with respect to nonstimulated cells onto randomly oriented fibers.…”
Section: Resultssupporting
confidence: 83%
“…Nevertheless, the combined effect of electrical and guidance cues was reported to enhance the neurite outgrowth in neuron‐like PC12 cells, stimulated through polypyrrole‐coated aligned sub‐micrometric fibers . In particular, enhancements in terms of fraction of neurite‐bearing cells (124%) and of neurite length (66% and 129%) were reported with respect to nonstimulated cells onto randomly oriented fibers. Results are not directly comparable since they were obtained for a different neuronal model and under different experimental conditions, in terms of stimulation protocols and electrical waveforms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of POP fibrous meshes being studied, however, mineral deposition was apparently accelerated under ES. Some studies have reported the applied ES could enrich the electric charge densities at the protruding cusps on rough-surfaced conductive PPY layer, 43,44 which was able to further enhance protein absorption, as confirmed by results shown in Figure 5. For the same reason, ES may improve ionic adsorption for electric charge on POP fibers.…”
Section: Discussionmentioning
confidence: 63%
“…As the most studied conductive polymer, PPy has been synthesized by chemical oxidation using a radical initiator with an appropriate electrolyte solution [59,60] or by electrochemical oxidation of pyrrole with an electrolyte solution on a platinum-coated electrode [61]. PPy has been reported to offer focal adhesion and the growth of various cell types associated with endothelial cells [62,63], neurons, supporting cells (DRG) [64][65][66], and rat pheochromocytoma (PC12) cells [66][67][68][69]. Yang et al devised conductive hydrogels of hyaluronic acid and PPy that enhanced mechanical and conductive properties [70] (Figure 4).…”
Section: Conductive Polymersmentioning
confidence: 99%